1979
DOI: 10.1530/jrf.0.0550463
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated and unconjugated oestrogens in fetal and maternal fluids of the cow throughout pregnancy

Abstract: Summary. The changes in concentration of oestrone, oestradiol (-17\g=a\ and -17\g=b\

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(49 citation statements)
references
References 12 publications
(18 reference statements)
6
42
0
1
Order By: Relevance
“…The sensitivity of these assay systems was approximately 30 pg/mL and the results were consistent. It was reported that the estrone sulfate concentration in bovine milk during gestation was lower than the detectable level in the first 80 to 90-day period and showed a sharp rise after day 100, which was consistent with the plasma concentration of estrone sulfate at the same gestational stage 1,10,15 . Based on the results of these reports and the present experiment, estrone sulfate can be detected in bovine milk before day 100.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The sensitivity of these assay systems was approximately 30 pg/mL and the results were consistent. It was reported that the estrone sulfate concentration in bovine milk during gestation was lower than the detectable level in the first 80 to 90-day period and showed a sharp rise after day 100, which was consistent with the plasma concentration of estrone sulfate at the same gestational stage 1,10,15 . Based on the results of these reports and the present experiment, estrone sulfate can be detected in bovine milk before day 100.…”
Section: Discussionsupporting
confidence: 78%
“…and milk increase gradually throughout gestation in the same way as those of free estrogens, and its level at each stage of gestation is the highest among all the estrogens, especially during the mid-to late periods of gestation 7,9,15 . Therefore, it is considered to be a practical indicator of placental function and has been used in pregnancy diagnosis 9,10 and in predicting the number of fetuses 1,17,20 .…”
Section: Jarq 37 (3) 2003mentioning
confidence: 92%
See 1 more Smart Citation
“…3) (Melampy et al, 1959) although some authors (MacDonald, McNutt & Nichols, 1953;Zimbelman, Loy & Casida, 1961;Ainsworth & Ryan, 1967) claim that negligible amounts of progestagens are synthesized by the bovine placenta. The corpus luteum of pregnancy produces large amounts of progesterone throughout the whole of pregnancy but a contribution by the placenta or the adrenals (Wendorf, Lawyer & First, 1983) Kamonpatana (1984); and for cows after Dobson & Dean (1974), Robertson (1974), Robertson & King (1979), Thatcher et al (1980) and Kaker et al (1984).…”
Section: Pubertymentioning
confidence: 99%
“…The fetal or cotyledonary portions of the bovine placentome are major sites of the synthesis and conjugation of estrogens during pregnancy [14]. Conversion between E1 and E1S and their concentrations in maternal plasma are controlled by enzymes, estrogen sulfotransferase and steroid sulfatase, located in the placentome [15].…”
mentioning
confidence: 99%